2015
DOI: 10.1017/s095026881500117x
|View full text |Cite
|
Sign up to set email alerts
|

Multistate outbreak of listeriosis caused by imported cheese and evidence of cross-contamination of other cheeses, USA, 2012

Abstract: Listeria monocytogenes is a foodborne pathogen that can cause bacteraemia, meningitis, and complications during pregnancy. In July 2012, molecular subtyping identified indistinguishable L. monocytogenes isolates from six patients and two samples of different cut and repackaged cheeses. A multistate outbreak investigation was initiated. Initial analyses identified an association between eating soft cheese and outbreak-related illness (odds ratio 17·3, 95% confidence interval 2·0-825·7) but no common brand. Chee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 30 publications
1
33
0
2
Order By: Relevance
“…This data set comprises 52 genomes for isolates of serotypes 1/2a and 1/2b and phylogenetically related serotypes (1/2c and 3). These 52 genomes include 20 outbreak-associated isolates representing 11 outbreaks and isolates from clinical, food, and environmental sources, for example, one isolate from an implicated production facility (ricotta salata) that matched a human case (12). We also included 17 additional genome sequences from isolates of serotypes 4b, 4d, and 4e to root the phylogenetic tree.…”
Section: Methodsmentioning
confidence: 99%
“…This data set comprises 52 genomes for isolates of serotypes 1/2a and 1/2b and phylogenetically related serotypes (1/2c and 3). These 52 genomes include 20 outbreak-associated isolates representing 11 outbreaks and isolates from clinical, food, and environmental sources, for example, one isolate from an implicated production facility (ricotta salata) that matched a human case (12). We also included 17 additional genome sequences from isolates of serotypes 4b, 4d, and 4e to root the phylogenetic tree.…”
Section: Methodsmentioning
confidence: 99%
“…Listeria monocytogenes, in particular, is frequently known to contaminate fresh cheese products, such as queso blanco cheese during their processing and post‐processing . It has been reported that L. monocytogenes can grow in commercial cheese products wrapped with polyethylene (PE) or low density polyethylene (LDPE) . In addition, cheese products without food preservatives such as butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) can be easily oxidized during storage …”
Section: Introductionmentioning
confidence: 99%
“…We estimate that 1 of 10,000 milkshakes would have a load >26,000 L. monocytogenes cells (95% CrI 15,600–240,000 L. monocytogenes cells). Assuming there was no initial contamination of the milkshake machines and no growth of the pathogen in the milkshakes, the mean contamination level of L. monocytogenes in the milkshakes (8 cells/g of ice cream) was relatively low compared with contamination levels in some other outbreaks ( 9 12 ). However, in the absence of leftovers from the actual implicated milkshakes, we cannot rule out the possibility that the 4 susceptible patients received some of the highest contaminated products from the factory line, triggering infection.…”
Section: Discussionmentioning
confidence: 99%